In silico analysis of resveratrol induced PD-L1 dimerisation - Urban, Viktor A.; Davidovskii, Alexander I.; Veresov, Valery G. (Experimental Biology and Biotechnology, 2021)
T-cell activation through the blockade of PD-1 – PD-L1 interactions is recognised at present as one of the most promising strategies in the cancer treatment and a number of antibodies targeting the PD-1 – PD-L1 immune checkpoint pathway have been approved after successful clinical trials. However, the use of antibodies suffers from a number of shortcomings including poor tissue and tumor penetration, long half-life time, poor oral bioavailability, and expensive production costs. Small molecule based therapeutic approaches offer the potential to address the shortcomings of the antibody-based checkpoint inhibitors. At present, more than twenty small molecular inhibitors of the PD-1 – PD-L1 interactions whose scaffold is based on substituted biphenyl group connected to a further aromatic ring through a benzyl ether bond have been identified and patented by Bristol – Mayers – Squibb (USA). Structural studies have shown that all these compounds act by inducing the dimerisation of PD-L1 that makes PD-L1 non-competent for forming complex with PD-1. Very recently, the dietary polyphenol resveratrol (RSV) has been reported to inhibit the PD-1 – PD-L1 interactions through the induction of the PD-L1 dimerisation but the mechanisms remain unclear. Here, computational structural biology tools combining protein – protein and protein – ligand docking with molecular dynamics simulations were used to gain structural insights into the mechanisms of the RSV-induced dimerisation of PD-L1.